Student-based brand equity in the business schools sector: An exploratory study - Vincent, Charles; Iona Gherman, Tatiana (CENTRUM Publishing, 2015)
Faced with increased competition, business schools seem to have realized that having the strongest brands, hence, a distinct image, is vital to strengthen their presence in the education marketplace. It is in this context that the present paper focuses on assessing the dimensions of brand equity of business schools from the MBA-enrolled student’s perspective, with a specific reference to the Peruvian market. In this regard, it builds an instrument around five dimensions of brand equity, namely, brand loyalty, brand association, brand awareness, perceived quality, and overall brand perception. Additionally, it furnishes a snapshot of the Peruvian business schools sector by means of providing the order of dimensions pertaining to each business school. The analysis suggests that perceived quality seems to be the most important dimension of brand equity, while the overall brand perception is almost always ranked last. Conceptualizing brand equity from the MBA-enrolled student’s perspective can prove to be useful as this framework could assist business schools in designing marketing strategies to improve their brand equity and gain a higher student share.
Keywords: Business schools; Brand loyalty; Perceived quality; Brand awareness; Brand association; Brand equity; Emerging markets; Factor analysis; Higher education; http://purl.org/pe-repo/ocde/ford#5.02.04